Patient and provider acceptance of telecoaching in type 2 diabetes: a mixed-method study embedded in a randomised clinical trial. Issue 1 (December 2016) - Odnoletkova, I.; Buysse, H.; Nobels, F.; Goderis, G.; Aertgeerts, B.; Annemans, L.; Ramaekers, D.
Abstract Background Despite advances in diagnosis and treatment of type 2 diabetes, suboptimal metabolic control persists. Patient education in diabetes has been proved to enhance self-efficacy and guideline-driven treatment, however many people with type 2 diabetes do not have access to or do not participate in self-management support programmes. Tele-education and telecoaching have the potential to improve accessibility and efficiency of care, but there is a slow uptake in Europe. Patient and provider acceptance in a local context is an important pre-condition for implementation. The aim of the study was to explore the perceptions of patients, nurses and general practitioners (GPs) regarding telecoaching in type 2 diabetes. Methods Mixed-method study embedded in a clinical trial, in which a nurse-led target-driven telecoaching programme consisting of 5 monthly telephone sessions of +/− 30 min was offered to 287 people with type 2 diabetes in Belgian primary care. Intervention attendance and satisfaction about the programme were analysed along with qualitative data obtained during post-trial semi-structured interviews with a purposive sample of patients, general practitioners (GPs) and nurses. The perceptions of patients and care providers about the intervention were coded and the themes interpreted as barriers or facilitators for adoption. Results Of 252 patients available for a follow-up analysis, 97.5 % reported being satisfied. Interviews were held with 16 patients, 17 general practitioners (GPs) and all nurses involved (n = 6). Themes associated with adoption facilitation were: 1) improved diabetes control; 2) need for more tailored patient education programmes offered from the moment of diagnosis; 3) comfort and flexibility; 4) evidence-based nature of the programme; 5) established cooperation between GPs and diabetes educators; and 6) efficiency gains. Most potential barriers were derived from the provider views: 1) poor patient motivation and suboptimal compliance with "faceless" advice; 2) GPs' reluctance in the area of patient referral and information sharing; 3) lack of legal, organisational and financial framework for telecare. Conclusions Nurse-led telecoaching of people with type 2 diabetes was well-accepted by patients and providers, with providers being in general more critical in their reflections. With increasing patient demand for mobile and remote services in healthcare, the findings of this study should support professionals involved in healthcare policy and innovation. Trial registration NCT01612520, registered prior to recruitment on 4th June 2012.